The Relationship Of Lead Levels To Enzym SGPT (Serum Glutamic Pyruvic Transaminase) Levels In The Blood At Public Refueling Station Operator In Gombel Semarang - Hunik Saryati (Universitas Widya Gama Mahakam Samarinda, 2023)
Abstract Background: Lead (Pb) is the most dangerous cause of air pollution. About 85% comes from motor vehicle emissions that affect lead levels in a person's blood. One of the groups that are at high risk of being directly exposed to lead pollutants in the air are people who carry out activities on the streets such as fuel filling stations (SPBU) operators. Objectives: This study aims to determine the levels of Lead (Pb) and SGPT in the blood and to determine the relationship between lead levels and blood levels of SGPT in gas station operators. Research Metodes: This research is analytical with a cross sectional study. The sampling technique used purposive sampling. The Population in this study was men aged 21 – 56 years. A total of 17 samples were conducted in purposive sampling. The data was analyzed with Spearman non parametric test. Results: The result of study obtained value of significance or Sig.(2-tailed) 0.116 > 0.05, This result states that there is no relationship between lead value and SGPT (Serum Glutamic Pyruvic Transaminase) value. Correlation coefficient value is – 0.396. express a weak linear relationship. Negative values indicate the opposite direction of the relationship, where the higher the lead value, the lower SGPT (Serum Glutamic Pyruvic Transaminase) value. Conclusion: Statistical test result obtained value of p (0.116) > α (0.05), it state that no significant association between lead and SGPT (Serum Glutamic Pyruvic Transaminase) in SPBU operators.